KINERJA BANK: Sudut Pandang Aktivitas, Kecukupan Modal, dan Tingkat Pendapatan - Sairin, Sairin; Sutoro, Moh. (Sekolah Menengah Kejuruan (SMK) Pustek, 2021)
As a profit institution, presenting good financial governance is a must. This is necessary, to demonstrate the company's ability to run a business, both in terms of operations, capital, or profits. This study aims to analyze the financial performance of the bank, through a study of business activities, capital adequacy and income levels. As well as to see how the company's revenue increases. To test this phenomenon, quantitative research methods are used with multiple regression analysis. The object of this research is the state commercial bank with the amount of data used is 40, through purposive sampling technique. The results showed that interest income was a determining factor for increasing banking income in Indonesia. This means that the optimization of credit activities will have a positive impact on bank revenue (in this case bank interest). However, the ratio of capital, credit, and operating costs during the 2010-2019 period has not shown a significant effect on the increase in company profitability.